ISLAMIC SPIRITUAL GUIDELINES (An Alternative Model to Improve Treatment Compliance with Type 2 Diabetes Mellitus Patients) - Sulistyo Andarmoyo (Jurnal Medika Hutama, 2020)
Medication adherence has an important role in therapeutic management in Type 2 Diabetes Mellitus patients. Patient's non-compliance with medication is often linked due to psychological factors, such as depression, anxiety, and eating disorders. One effort to improve medication adherence is the awareness of patients about health problems and this can be done by giving Islamic Spiritual Guidance, which is a treatment or healing of psychological disorders that are carried out systematically based on the concepts of the Qur'an and As-Sunnah. Islamic Spiritual Guidance is proven to be effective in influencing the handling of psychological disorders in patients and is believed to also be able to enforce medication adherence in patients with type 2 diabetes mellitus. Spiritual therapy is very influential to build a sense of self-acceptance so that patients will be obedient in following the advice of health workers, one of which is being obedient in undergoing medication.